SELEKSI PREDIKTOR PADA REGRESI LOGISTIK - Hendarti, Dwiastusi
Abstract : Selection of meaningful predictor for statistical model is an important step in model building. Selection in Logistic Regression can be done through Deviance Analysis, Cp Mallows and AIC criterion. Birth rate and Toxoplasmosis data use here as an ilustration.